The Effect of Personality Traits on Procrastination and Cognitive Failures - Kamboj, Ankitdeep (My University, 2018)
Personality traits are defined as a set of characteristics that define an individual’s personality. A cognitive failure is an inability to complete a task, which a person can complete without any mistakes and difficulty. The habit of delaying or postponing of work and important tasks is known as procrastination. The present work is an attempt to know whether personality traits effect procrastination and cognitive failures. The study also explored gender differences in personality traits, cognitive failures (including all its facets) and procrastination. The total of 160 (80 males, 80 females) college students voluntarily participated in the study by signing a consent form. The subjects administered the NEO-FFI personality questionnaire, Lay’s Procrastination scale and Cognitive Failure Questionnaire. The results were subjected to Pearson’s correlation, linear regression and t test analysis. The results exhibited that procrastinating behaviour was correlated to a single trait of personality, i.e. conscientiousness. The cognitive failures had a correlation with agreeableness and conscientiousness. Memory exhibited a correlation with conscientiousness and neuroticism. Distractibility was correlated to conscientiousness, agreeableness and neuroticism. Blunders exhibited a strong relationship with agreeableness and conscientiousness. Names correlated with a single trait of personality, i.e. conscientiousness. The t-test results highlight gender differences in neuroticism, conscientiousness, CFQ Total, distractibility, blunders, names and procrastinating behaviour.
Keywords: Personality traits; cognitive failures; procrastination; gender differences